Multi-omics bioactivity profile-based chemical grouping and read-across: a case study with Daphnia magna and azo dyes - Hanna Gruszczynska; Rosemary E. Barnett; Gavin R. Lloyd; Ralf J. M. Weber; Thomas N. Lawson; Jiarui Zhou; Elena Sostare; John K. Colbourne; Mark R. Viant (Archives of Toxicology, 2024)
Grouping/read-across is widely used for predicting the toxicity of data-poor target substance(s) using data-rich source substance(s). While the chemical industry and the regulators recognise its benefits, registration dossiers are often rejected due to weak analogue/category justifications based largely on the structural similarity of source and target substances. Here we demonstrate how multi-omics measurements can improve confidence in grouping via a statistical assessment of the similarity of molecular effects. Six azo dyes provided a pool of potential source substances to predict long-term toxicity to aquatic invertebrates ( Daphnia magna ) for the dye Disperse Yellow 3 (DY3) as the target substance. First, we assessed the structural similarities of the dyes, generating a grouping hypothesis with DY3 and two Sudan dyes within one group. Daphnia magna were exposed acutely to equi-effective doses of all seven dyes (each at 3 doses and 3 time points), transcriptomics and metabolomics data were generated from 760 samples. Multi-omics bioactivity profile-based grouping uniquely revealed that Sudan 1 (S1) is the most suitable analogue for read-across to DY3. Mapping ToxPrint structural fingerprints of the dyes onto the bioactivity profile-based grouping indicated an aromatic alcohol moiety could be responsible for this bioactivity similarity. The long-term reproductive toxicity to aquatic invertebrates of DY3 was predicted from S1 (21-day NOEC, 40 µg/L). This prediction was confirmed experimentally by measuring the toxicity of DY3 in D. magna . While limitations of this ‘omics approach are identified, the study illustrates an effective statistical approach for building chemical groups.

P22-23: Expediting the uptake of Next-Generation Risk Assessment (NGRA) into EU chemicals legislation under PARC - M. Herzler; I. Apruzzese; N. Bandow; F. Busquet; A. Cavoski; J. Colbourne; E. Di Consiglio; M. Dusinska; G. Flingelli; L. Holden; R. Hornek-Gausterer; A. Kaiser; et al. (Toxicology Letters, 2023)

Identification of the type locality of the South Island Brown Kiwi Apteryx australis - R. P. Scofield; J. R. Wood; L. de Nascimento; H. A. Robertson; R. M. Colbourne; V. L. De Pietri; J. Innes; J. T. Weir (Conservation Genetics, 2021)

Acetazolamide Mitigates Intracranial Pressure Spikes Without Affecting Functional Outcome After Experimental Hemorrhagic Stroke - Michael R. Williamson; Cassandra M. Wilkinson; Kristen Dietrich; Frederick Colbourne (Translational Stroke Research, 2019)

Cryptic inbreeding depression in a growing population of a long‐lived species - Helen R. Taylor; Rogan M. Colbourne; Hugh A. Robertson; Nicola J. Nelson; Fred W. Allendorf; Kristina M. Ramstad (Molecular Ecology, 2017)
Genetic effects are often overlooked in endangered species monitoring, and populations showing positive growth are often assumed to be secure. However, the continued reproductive success of a few individuals may mask issues such as inbreeding depression, especially in long‐lived species. Here, we test for inbreeding depression in little spotted kiwi ( Apteryx owenii ) by comparing a population founded with two birds to one founded with 40 birds, both from the same source population and both showing positive population growth. We used a combination of microsatellite genotypes, nest observations and modelling to examine the consequences of assessing population viability exclusively via population growth. We demonstrate (i) significantly lower hatching success despite significantly higher reproductive effort in the population with two founders; (ii) positive growth in the population with two founders is mainly driven by ongoing chick production of the founding pair; and (iii) a substantial genetic load in the population founded with two birds (10–15 diploid lethal equivalents). Our results illustrate that substantial, cryptic inbreeding depression may still be present when a population is growing, especially in long‐lived species with overlapping generations.